PENGENDALI PERSONAL KOMPUTER LABORATORIUM DENGAN MEMANFAATKAN BARCODE IDENTITAS MAHASISWA PADA KARTU TANDA MAHASISWA UNTUK MEMBANTU MANAJEMEN PENGGUNAAN LABORATORIUM - Dian Nathasia, Novi (JURNAL TEKNOLOGI INFORMASI: Teori, Konsep, dan Implementasi, 2011)
Student Identity Card (KTM) currently more widely used than as identification of any student, but the KTM development is expected to be used as a tool that has many functions, such as cards such as campus computer labs and perhaps as a payment card as an ATM card. Utilization KTM to access the on-campus facilities such as computers in the lab can be done by adding lines of code on the card and the barcode sensor which is used as input devices to capture lines of code. The catch line of code is then processed by using software control system switches off the personal computer on which is then used to turn on and off the computer at the laboratory according to a predetermined time. Switch on-off control system is not only a personal computer in the form of software, but also comprises a control computer and the relay driver circuit in charge of moving the switch on off personal computers. To integrate the computer controlling the relay driver circuit, used card PPI (Pheripheral Programable Interface) as interface 8255. Keywords: Personal Computer, Sensor bar codes, PPI 8255, Student Identity Card (KTM).